Revenge and gender in classical, medieval and Renaissance literature - Dawson, Lesel; McHardy, Fiona (Edinburgh scholarship online., 2018)
This collection explores a range of literary and historical texts from ancient Greece and Rome, medieval Iceland and medieval and early modern England to provide an understanding of wider historical continuities and discontinuities in representations of gender and revenge.